OTTOMAN ARMENIANS WHO MIGRATED SOUTH AMERICAN CONTINENT - Adem KARA (Fırat University, 2019)
Topics examined in the context of the Ottoman Empire, as well as migration of America, South America, mainly in Argentina, Chile and Brazil, countries such as Uruguay is made. Here is a Sephardic ancestors and the Armenian community lives in the large Ottoman subjects. XX. Beginning of the century immigrants around here to take ownership of their ancestral ananelerini regard to this generation of sustained work is also very sensitive. Turkish society, transnational mass migrations that occurred since 1900, the most important reason is economical, transnational Turkish immigrants in the United States and South America to earn money, she and her family have gone to in order to raise the level of prosperity. However, the migration of both the Turkish labor movement of the population, predominantly rural in origin and unskilled.